Review of the Effects of Additives on Biodiesel Properties, Performance, and Emission Features - Obed M., Ali; R., Mamat; C. K. M., Faizal (American Institute of Physics (AIP), 2013)
As a renewable, sustainable and alternative fuel for compression ignition engines, biodiesel is widely accepted as comparable fuel to diesel in compression ignition engines. This is due to several factors like decreasing the dependence on imported petroleum; providing a market for the excess production of vegetable oils and animal fats; using renewable and biodegradable fuels; reducing global warming due to its closed carbon cycle by CO2 recycling; increasing lubricity; and reducing substantially the exhaust emissions of carbon monoxide, unburned hydrocarbons, and particulate emissions from diesel engines. However, there is a major drawback in the use of biodiesel as low heating value and NOX tends to be higher. On the other hand, its relatively poor low-temperature flow properties are a characteristic of biodiesel which limits its application. Here, fuel additives become indispensable tools not only to decrease these drawbacks but also to produce specified products that meet the international and regional standards. This article is a literature review of the effect of different additives on biodiesel properties, performance, and emission characteristics. The researches published by different journals are cited preferentially. From these researches, the effect of biodiesel additives on fuel cold flow properties, engine power, fuel economy and emissions including regulated and non-regulated emissions, and the corresponding effect factors were surveyed and analyzed in detail. Varying results of improvement in cold flow properties have been obtained by using different additives. Similarly, different additives were used by different researchers to improve the performance of a compression ignition engine and its emissions. This review was taken up to identify the various additives used to improve the cold flow properties of biodiesels and improve the performance of a diesel engine and its emissions while using additive blended biodiesels. The review concludes that the additive usage in biodiesel is inseparable both for improving the cold flow properties and for better engine performance and emission control. Further research is needed to develop biodiesel specific additives.